The role of family ownership in the relationship between board characteristics and corporate social environmental reporting : evidence from Malaysia - Fathyah Hashim; Zaini Embong; Wang, Boon Phoey (Penerbit Universiti Kebangsaan Malaysia, 2021)
The objective of this paper is to investigate the role of family ownership in the relationship between board of directors (BOD) characteristics and the reporting of corporate social and environmental practices (CSER). BOD is one of the corporate governance mechanism put in place to ensure that the company is managed to the best interest of shareholders. However, previous findings on the relationship between BOD characteristics and CSER are inconclusive. The effectiveness corporate governance mechanisms including BOD characteristics is claimed to be influenced by cultural and societal norms. Hence, this study adds to the understanding of the role of BOD in reporting practices of companies in Malaysia. In addition, given the mixed findings on the relationship of BOD and CSER, this study also investigates the role of family ownership. This paper suggests that the relationship between BOD and CSER is weaker in family-owned companies because the owner tends to safeguard the information, hence lower disclosure is evidenced. Malaysia is unique in the sense than around 70% of companies are owned by families and this provide a good setting for the study. Cross-sectional sample of 136 public listed companies are selected using systematic stratified random sampling methods. BOD characteristics to be investigated are female on Board (FB), board independence (BI), board size (BS) and CSR committee (CC). The CSER is assessed by content analysis, and PLS-SEM is used for data analysis. The results indicate that all of the BOD characteristics tested in this study except for board size, have significant positive relationship with CSER. However, the moderating role of family ownership is not supported.